The Review of Transaction Sale Juridical Bring Through The Instragram - Sengaji Sengaji (Veteran Justice Journal, 2019)
This aims to find out How to Purchase Transactions Effects Online Through Instagram Media and How to Remedy The aggrieved party in buying and selling online through Instagram media. This study uses a normative research method with data collection techniques used to solve the problem formulation, namely the literature data obtained based on legislation and literature or official books. Analysis of the data used is a qualitative approach to primary data and secondary data. The results of the study can be concluded that the rights and obligations of the parties who made a sale and purchase agreement through the Instagram media can bring about a result of the agreement. From this we can know which obstacles arise from the rights and obligations of the sale and purchase agreement. And if a dispute has occurred, then legal protection can be carried out preventively and repressively. And can be continued with efforts to resolve the dispute.